Acondicionamiento acústico y electroacústica del estudio de TV de Canal Uno - Villavicencio Sotomayor, Danny Fernando (2010)
The research work present has for object to give an idea of the quality audio has Ecuadorian television, focusing specifically on the acoustic and electroacoustic giving an adequate string should have a television set, this work is a fundamental contribution for career students and people who are involved on television and especially audio, can developed other topics such as electroacoustic for mobile units and infinite topics than may arise from a thesis topic as is an acoustic and electroacoustic conditioning of a television studio. The University of Americas as this create high quality professionals, always innovating and promoting, careers and students, giving the University a stellar level within the city and country, therefore, is important enhancement of our university have quality professionals in important work and good salary. It should be noted that this work was done with the help of the company Canal UNO, which provides its premises for development, and people using knowledge of the environment.